Determination of sterilization method and effect of 6-benzylaminopurine and α-Naphthalene acetic acid on shoot formation of Clinacanthus nutans - Saw, Siew Fen (2015)
The herb plant from the family Acanthaceae called Clinacanthus nutans (Burm. f.) Lindau or better known as Sabah Snake Grass has been commercialized recently. It is native to Southeast Asia, including Indonesia, Thailand, and Malaysia. The leaves are believed to be able to treat insect bites, herpes infection, nettle rash, allergic responses and recently it is well known for its healing properties such as a cure for cancer and kidney failure alleviation. The objectives of this study were to establish the best sterilization method and to determine the best combination of BAP and NAA for optimizing the in vitro shoot formation of C. nutans. The explants for this study were the nodes. In the determination of sterilization method, treatment with 30% Clorox for 30 min immersion time resulted in the least contamination, however some of the explants were damaged and unable to produce shoots after 4 to 6 weeks of culture. By using 30% Clorox at 20 min immersion time, resulted in 67.67% survived, non-contaminated explants. The protocol needs to be further refined to improve the effectiveness of killing the contaminants. For the shoot regeneration study, almost all the explants (99.96%) produced shoots successfully. Treatment consisting of 10 mg/L BAP without NAA produced the highest mean number of shoots (3.17) per explant, that reached a mean height of 0.73 cm and produced mean number of 13.56 leaves per shoot after 8 weeks of culture.